The Validity of Notary Public Deeds in the Capital Market During a Vacuum of License Due to the Retroactive Cancellation of Registration Certificates by the Financial Services Authority - Tanaya, Velliana; Hasianatama, Tri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The increasingly significant Indonesian capital market demands a vital role from supporting professions like Capital Market Notaries to ensure legal certainty and compliance. The Financial Services Authority Regulation (POJK) Number 67/OJK.04/2017 mandates the re-registration of the Registered Certificate (STTD), but its implementation triggered an administrative crisis that led to the cancellation of 1066 Notary STTDs, creating a period of "vacuum of license". To assess the impact of this implementation, research is needed on the validity of Notary deeds created during the vacuum of license and the analysis of legal protection provided to the Notary and relevant parties (issuers/investors). This study employs a normative juridical method with a case study approach, referencing the State Administrative Court (PTUN) Decision Number 38/G/2020/PTUN.JKT. The research findings conclude that deeds made by the Notary during the vacuum of license period are vulnerable to legal uncertainty and potentially downgraded to private deeds (underhand documents). However, the PTUN decision indicates that OJK's action cannot fully guarantee legal certainty as it was deemed procedurally flawed and violated the General Principles of Good Governance (AUPB). The implementation of the STTD cancellation regulation failed to realize the objective of providing protection for Notaries and capital market stakeholders, because the Notary and the parties using the deed (issuers/investors) are entitled to legal protection if they can prove compliance with administrative obligations (STTD re-registration).